Conception of Absolute and Relative Space in Philosophy and Their Relationship to the Territoriality of the Modern State (Czech Journal of International Relations, 2010)
The paper seeks to find the relationship between the philosophical debateon absolute and relative space and the IR debate on territoriality. It showsthe relation between the absolute space concept and the territorialdefinition of the modern state. It also seeks to find parallels betweenrelativity and relative space on one hand and the current questioning ofterritoriality and attempts to find a substitute for it on the other. Due to thefact that relativity has not been overthrown in philosophy of physics, thearticle concludes that we cannot expect a relative conception of space todisappear from IR either.
Keywords: State; territoriality; space; absolute space; relative space